Factors Contributing to Violence Against Children: Insights From a Multi-informant Study Among Family-Triads From Three East-African Refugee Camps - Hecker, Tobias (Journal of interpersonal violence, 2022)
Parental violence poses a considerable, yet mitigable risk for the mental health and well-being of refugee children living in resource-poor refugee camps. However, little is known about potential risk factors for parental violence in these settings. Using an ecological systems perspective and a multi-informant approach, we investigated ontogenic (parental childhood experiences of violence), microsystem (parents? and children?s psychopathology) and exosystem (families? monthly household income) risk factors for child-directed parental violence in a sample of 226 Burundian families living in refugee camps in Tanzania. Data were collected through individual structured clinical interviews with mothers, fathers, and children. In the child-report path model [?2 (6) = 7.752, p = .257, comparative fit index (CFI) = 0.99, root mean square error of approximation (RMSEA) = 0.036 (p = .562)], children?s posttraumatic stress disorder (PTSD) symptoms, externalizing symptoms and paternal PTSD symptoms were positively associated with violence by both parents. Maternal psychosocial impairment was positively associated with child-reported paternal violence. In the parent-report path model [?2 (6) = 7.789, p = .254, CFI = 0.97, RMSEA = 0.036 (p = .535)], children?s externalizing problems as well as a lower monthly household income were positively related to maternal violence. Each parent?s childhood victimization was positively linked to their use of violence against children. Maternal psychosocial impairment and paternal alcohol abuse were positively associated with paternal violence. Child and paternal psychopathology, maternal psychosocial impairment, parents? childhood victimization, and families? socioeconomic status may be important targets for prevention and intervention approaches aiming to reduce parental violence against refugee children living in camps.